2022
DOI: 10.3390/pr10061205
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Multiple-Criteria Decision-Making Model for New Product Development: The Case of Taiwan Organic Light-Emitting Diode Industry

Abstract: Due to the strong demand for organic light-emitting diode (OLED) display products and the highly competitive global market, OLED enterprises need to proactively make product innovations for presuming business competitive advantage, high sales, high profits, high customer consuming value, and the sustainability of the enterprise. A suitable multi-criteria decision-making (MCDM) model for OLED new product development (NPD) can help OLED enterprises’ R&D team to minimize risks and maximize the success rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Additionally, in the ACTIVITY construct, other variables, such as the acquisition of knowledge through external sources [31] and that organizational and financial aspects facilitate the development of technological innovation activities [34], are the ones that follow, obtaining a CR of 0.665 and 0.674, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in the ACTIVITY construct, other variables, such as the acquisition of knowledge through external sources [31] and that organizational and financial aspects facilitate the development of technological innovation activities [34], are the ones that follow, obtaining a CR of 0.665 and 0.674, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We launched a 34-question questionnaire to a sample of 56 exporting SMEs in the Colombian Caribbean. At the end of the survey, the activities and product innovation that are related to the performance of SMEs showed that the activities are related to the following: Investment in Research and Development (30), Acquisition of knowledge from external sources (31), Technological Component (Infrastructure and Investment) (33), Financial and Operational Aspects (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation